Supplementation of Slow‐Release Melatonin Improves Recovery of Ovarian Cyclicity and Conception in Summer Anoestrous Buffaloes (Bubalus bubalis). Issue 1 (13th November 2015) - Kumar, A; Mehrotra, S; Singh, G; Maurya, VP; Narayanan, K; Mahla, AS; Chaudhari, RK; Singh, M; Soni, YK; Kumawat, BL; Dabas, SK; Srivastava, N
Contents: The role of melatonin as a protective neurohormone against restoring cyclicity in summer anoestrous animals in photoperiod species has gained wider acceptance. This study was designed to uncover the evidence the slow‐release melatonin (MLT) has on initiation of ovarian cyclicity and conception rate (CR) in summer anoestrous buffaloes. Thus, buffaloes diagnosed as summer anoestrous (absence of overt signs of oestrus, concurrent rectal examination and radioimmunoassay for serum progesterone at 10 days interval) were grouped as untreated (Group I, sterilized corn oil, n = 8) and treated (Group II, single subcutaneous injection of MLT @18 mg/50 kg bwt in sterilized corn oil, n = 20). Animals treated and detected in oestrus were artificially inseminated (AI) followed by division into Group III (second dose of MLT on 5th day post‐AI, n = 8) and Group IV (no melatonin administration, n = 10). Blood samples were collected at 4 days interval for estimation of serum MLT, progesterone and oestrogen using radioimmunoassay kit. Mean oestrous induction rate (OIR), oestrous induction interval (OII), interoestrous interval (IOI) and CR were estimated. Compared to control, concentration of melatonin was significantly (p < 0.05) higher in treated group ranging from 14.34 ± 1.72 to 412.31 ± 14.47 pg/ml whereas other two hormones did not show any concentration difference. Melatonin‐administered buffaloes showed significantly (p < 0.05) higher (90%) OIR with OII of 18.06 ± 1.57 days. Results showed improvement in conception rate in buffaloes administered with post‐insemination melatonin. It can be concluded from the study that slow‐release melatonin supplementation restored cyclicity in summer anoestrous animals resulting in improvement in conception rate in buffaloes.